PRELIMINARY PHYTOCHEMICAL AND PHENOLIC CONTENT OF STEMS BARK OF ABELMOSCHUS MANIHOT (LINN.) MEDIK - S., Chumbhale D.; R., Chaudhari S.; D., Upasani C. (Asian Journal of Pharmaceutical Research and Development, 2013)
The present study was designed to determine the phytochemical properties and phenolic content of various extracts of the Abelmoschus manihot (Linn.) Medik (A. manihot) is an important medicinal plant in Indian traditional system of medicine. Phenolic content of A. manihot stems bark extracts was determined by Folin-coutigue reagent test. The extractive values of petroleum ether, methanolic, ethyl acetate soluble fraction of methanolic extract, ethyl acetate insoluble fraction of methanolic extract and aqueous extract were found to be 3.75%, 8.00%, 3.80%, 4.20%, 8.44% w/w respectively. Preliminary phytochemical analysis mainly revealed the presence of carbohydrates, glycosides, flavonoids, tannins, steroids and proteins in methanolic, ethyl acetate soluble fraction of methanolic extract, ethyl acetate insoluble fraction of methanolic extract and aqueous extracts. Petroleum ether extract shows positive result for the fixed oil and fats, saponin and phytosterol. Phenolic content of petroleum ether, methanolic, ethyl acetate soluble fraction of methanolic extract, ethyl acetate insoluble fraction of methanolic extract and aqueous extracts were found to be 16.00%, 24.00%, 28.00%, 28.00%, 38.00%, 32.00% respectively. Present study of preliminary phytochemical screening and phenolic content of A. manihot stem bark provide useful information which may help in authenticating the genuine plant along with nature of phytoconstituents present in it. These findings will be useful towards further isolation of phytoconstituents from various extract of A. manihot stems bark and support for the safe use of this traditional plant.